The sea floor : an introduction to marine geology - Seibold, Eugen (Springer, 2010)
Origin and morphology of ocean basins -- Origin and morphology of ocean margins -- Sources and composition of marine sediments -- effects of waves and currents -- Sea level processes and effects of sea level change -- Productivity and benthic organisms-distribution, activity, and environmental reconstruction -- Imprint of climatic zonation on marine sediments -- Deep-sea sediments-patterns, processes, and stratigraphic methods -- Paleoceanography- the deep-sea record -- Resources from the ocean floor.